2011
DOI: 10.1590/s1678-58782011000100012
|View full text |Cite
|
Sign up to set email alerts
|

A water flow pattern analysis of Guajará Bay: Amazon Estuary - Brazil

Abstract: This work describes the steps required to construct a hydrodynamic model of the Guajará

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…The higher levels of conductivity and concentrations of N-compounds at stations S3, S4, S6 and S7 were related to the organic matter and domestic wastes poured into the bay. It is suggested that the higher concentrations of NO 3 (compatible with the ichthyoplankton life) in a stretch where currents are weaker (Barros et al 2011) contributed to the higher larval diversity and to the approximation to the city of post-flexion clupeiforms. Ammonia levels of toxicity for fish vary considerably with pH, temperature, dissolved oxygen, taxa and development stages (Vosylienë & Kazlauskienë 2004, Eddy 2005.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher levels of conductivity and concentrations of N-compounds at stations S3, S4, S6 and S7 were related to the organic matter and domestic wastes poured into the bay. It is suggested that the higher concentrations of NO 3 (compatible with the ichthyoplankton life) in a stretch where currents are weaker (Barros et al 2011) contributed to the higher larval diversity and to the approximation to the city of post-flexion clupeiforms. Ammonia levels of toxicity for fish vary considerably with pH, temperature, dissolved oxygen, taxa and development stages (Vosylienë & Kazlauskienë 2004, Eddy 2005.…”
Section: Discussionmentioning
confidence: 99%
“…The deepest areas and stronger currents are encountered at the Onça Island Channel, on the left margin of the Guajará Bay (Figure 1) and at the Guamá River main channel, on the right-hand side of the river bed. In comparison, water currents at the city waterfront are weaker, preventing large dispersion of contaminants poured in the bay (Barros et al 2011). Further data on the hydrodynamic of the Guajará Bay and Guamá River are available in Barros et al (2011) and Bezerra et al (2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the Belém embankment, a classic shallow-water twodimensional hydrodynamic model was used, calibrated by Barros et al (2011) with respect to free-surface elevation above mean water level. However, validation with observed data was necessary to assess model accuracy with respect to the simulated velocities.…”
Section: Hydrodynamic Modelmentioning
confidence: 99%
“…In the Amazon estuary region, where the tidal range is up to 4 m, interactions between the river and oceanic flows and the local morphology combine to produce a complex flow pattern around the city of Belém in Brazil (Barros et al, 2011).…”
Section: Introductionmentioning
confidence: 99%